2011
DOI: 10.1080/11250003.2011.598350
|View full text |Cite
|
Sign up to set email alerts
|

A revision of the deep-sea genus Axiokebuita Pocklington and Fournier, 1987 (Annelida: Scalibregmatidae)

Abstract: The deep-sea genus Axiokebuita (Annelida, Scalibregmatidae) has hitherto been considered to contain two species, Axiokebuita minuta (Hartman, 1967) and Axiokebuita millsi Pocklington and Fournier, 1987, each rarely recorded in the literature and both supposedly having bipolar distributions. From the study of some types, other museum collection material, plus newly collected specimens from the slope depths of the Bellingshausen Sea and off the Antarctic Peninsula (Antarctica), Iceland and Iberian Peninsula, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…This character is an additional aspect of the overall morphology of scalibregmatids that deserves further study. The recent papers by Parapar et al (2011b) and Martínez et al (2013Martínez et al ( , 2014 on two closely related scalibregmatid genera, Axiokebuita and Speleobregma, suggest that a ventral groove or ridge line is completely absent in all described species of these two genera. If so, then, in conjunction with the complete absence of lyrate setae, acicular spines, branchiae, and parapodial cirri, together with the presence of an unusual prostomium with long ciliated lateral horns (termed palps by these authors) and an unusual peristomial sensory structure, this clade as reported by these authors differs considerably from other scalibregmatids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This character is an additional aspect of the overall morphology of scalibregmatids that deserves further study. The recent papers by Parapar et al (2011b) and Martínez et al (2013Martínez et al ( , 2014 on two closely related scalibregmatid genera, Axiokebuita and Speleobregma, suggest that a ventral groove or ridge line is completely absent in all described species of these two genera. If so, then, in conjunction with the complete absence of lyrate setae, acicular spines, branchiae, and parapodial cirri, together with the presence of an unusual prostomium with long ciliated lateral horns (termed palps by these authors) and an unusual peristomial sensory structure, this clade as reported by these authors differs considerably from other scalibregmatids.…”
Section: Discussionmentioning
confidence: 99%
“…As noted earlier this paper, the scalibregmatids from Antarctic seas are well known from the works by Hartman (1967), Blake (1981), Schüller & Hilbig (2007), and Schüller (2008).The three new species of scalibregmatids described here bring to 15 the number of species known from Antarctic seas, all endemic. However, Parapar et al (2011b) recently synonymized Axiokebuita millsi Pocklington & Fournier 1987, a deep-water species from the northern hemisphere, with A. minuta (Hartman, 1967), a deep-water species from Antarctica, thus producing a potential bipolar deep-water species. Known species of Scalibregmatidae from Antarctic seas are listed in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…They all have short bodies with < 25 trunk segments, a unique bilobed, globular, adhesive pygidium, as well as two elongated and densely ciliated nuchal organs (Parapar et al . ). Their habitat is also very different from that of other Scalibregmatidae.…”
Section: Introductionmentioning
confidence: 97%
“…The four nominal species in these genera instead of horns possess extended ventral palps with motile, dense, ciliary bands that produce water currents (Bertelsen ; Pocklington and Fournier ; Persson and Pleijel ; Parapar et al . ; Martínez et al . ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation